Transnational practices in communities of task and communities of learning. Issue 5 (November 2014) - Hydle, Katja M; Kvålshaugen, Ragnhild; Breunig, Karl Joachim
This article explores situated practices in communities that provide transnational services. Communities of practice generally focus on reinforcing local ties. Our study identifies two distinctive but interdependent communities of practice that are transnational and virtual: one community consists of employees who share work and tasks, labeled communities of task; the other consists of employees who jointly share and create knowledge, labeled communities of learning. We extend the existing community of practice literature by providing a heterogeneous understanding of the different types of situated practices, claiming that the situated practices of sharing work and sharing knowledge stem from the type of participation within the communities, either through service relays or virtual servicing. Empirical data in this study were collected from two transnational professional service firms. Our study shows that both types of communities benefit from managerial facilitation, even though one community type is more formal and the other is informal.